THE EFFECT OF USING AUGMENTED REALITY IN THE STUDENTS’ SPEAKING SKILL - Chaidir, Eli Nofriati; As’ari, Chalil; Dewi, Silvi Listia; Sriwinar, Sriwinar (University of Muhammadiyah Malang, 2024)
Implementation of Independent Curriculum requires teachers must be able to use digital media to create classroom more active, innovative, enjoyable, and can improve students’ learning outcomes. However, students' speaking skills at SMA Negeri 1 Gandapura are still low due to the teacher not yet utilizing digital media optimally in teaching speaking. This study aims to determine the effectiveness of using Augmented Reality (AR) media in improving students' speaking skills. This research used an experimental method and the sample of the research was taken two classes; class XI Merdeka 1 as control group and class XI Merdeka 2 as experimental group. The research instrument used was pre-test and post-test. The collected data was analyzed using inferential statistics with a t-test, through SPSS version 16 software. The finding was the students’ average pre-test speaking score in the experimental class was 69.7, while the average post-test score was 72.3. In conclusion, the use of AR media is effective and can enhance students' speaking skills.